Success Rate Comparison of Nasolacrimal Duct Probing with and without Assistance of Nasal Endoscope in Congenital Nasolacrimal Duct Obstruction - Hussain, Irshad; Khan, Shafaq Pervez; Alam, Masood; Abbas, Asim; Khan, Faisal Aziz (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the success rate of nasal endoscopic assisted probing and simple probing in congenital nasolacrimal duct obstruction.Study Design: Quasi-experimental study.Place and Duration of Study: Eye department, Combined Military Hospital, Malir Cantt, Karachi, from Feb 2018 to Jun 2019.Methodology: A total of 100 children were randomly divided into two groups. Each child in both groups underwent probing of the nasolacrimal duct. In one group, simple probing was performed, and patency was confirmed with metal on metal touch. In the second group, a nasal endoscope was employed to visualize probe passage through the opening of the nasolacrimal duct in the inferior meatus. In fracture of the inferior turbinate was performed in every case when a nasal endoscope was utilized. In the simple probing group, in fracture was performed if the inferior meatus was narrow. The rate of epiphora resolution was recorded in both groups at 1-month postoperatively. Results: The success rate of epiphora resolution was 96% (48 out of 50) in the nasal endoscopic assisted probing-group and 82% (41 out of 50) in the simple probing-group (p=0.02). The simple probing-group had a 40% (20 out of 50) significant nasal bleed, and in the nasal endoscopic-group, the significant nasal bleed was 20% (10 out of 50) (p=0.02).Conclusion: Nasal endoscopic assisted probing of the nasolacrimal duct has a higher success rate than simple probing in congenital nasolacrimal duct obstruction.